2015
DOI: 10.1038/leu.2015.115
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of azacitidine in unselected high-risk myelodysplastic syndromes: results from the Spanish registry

Abstract: The benefit of azacitidine treatment in survival of high-risk myelodysplastic syndromes (MDS) patients compared with conventional care treatment (CCT) has not been established outside clinical trials. To assess its effectiveness, we compared overall survival (OS) between azacitidine and conventional treatment (CCT) in high-risk MDS patients, excluding those undergoing stem cell transplantation, submitted to the Spanish MDS registry from 2000 to 2013. Several Cox regression and competing risk models, considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
79
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(88 citation statements)
references
References 22 publications
7
79
2
Order By: Relevance
“…Data entry into a study-specific eCRF is performed by clinical trial personnel and/or the treating physicians, after the collection of patient written informed consent from all patients alive at the time of data entry. In contrast, other study groups have collected data from all patients diagnosed with MDS/AML [24] within registries or compassionate use programs approved by internal review boards [35], with informed patient consent. Some have also used anonymised minimal datasets of the entire country population obtained via medical claims from healthcare insurance companies and/or national cancer and/or leukaemia registries to assess treatment of patients with MDS and/or AML [5,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data entry into a study-specific eCRF is performed by clinical trial personnel and/or the treating physicians, after the collection of patient written informed consent from all patients alive at the time of data entry. In contrast, other study groups have collected data from all patients diagnosed with MDS/AML [24] within registries or compassionate use programs approved by internal review boards [35], with informed patient consent. Some have also used anonymised minimal datasets of the entire country population obtained via medical claims from healthcare insurance companies and/or national cancer and/or leukaemia registries to assess treatment of patients with MDS and/or AML [5,36,37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, caution needs to be exercised when using newly-approved drugs in patients who would not have met clinical trial inclusion criteria, and conclusions drawn from clinical trials cannot eo ipso be generalized to all patients with AML. In fact, experts in the field have recently ascertained that all trial results should be extrapolated with caution, and population-based studies of real-world patients have a prominent role in examining the prognosis, as well as the management, efficacy and toxicity of new agents after regulatory approval and outside of clinical trials of higher-risk MDS [24,25] and AML [26]. …”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the OS benefit in patients treated with azacitidine was shown via meta-analysis [28]. However, a recent study in Taiwan reported that a better outcome with azacitidine treatment was only observed for the IPSS-R very high risk group (median OS, 15.2 months vs. 7.5 months) [19]; additionally, in another study of 821 patients with higher-risk MDS in Spain, no significant advantage for azacitidine-treated patients was observed in terms of OS or LFS [29]. The reason for this difference between randomized clinical trials and population based studies is unclear; thus, identification of the biological and clinical variables related to HMA response is of value.…”
Section: Discussionmentioning
confidence: 99%
“…15 Patients with HR-MDS usually are referred to tertiary centers early in the disease course only if alloHSCT is considered or after HMA failure; the rare younger patient with MDS and those with unusual presentations such as MDS/myeloproliferative neoplasm overlapping syndromes also are more likely to be referred. [8][9][10][11][18][19][20][21][22][23][24][25][26][27] For example, investigators in the MDS Clinical Research Consortium recently described the outcomes of patients in what to our knowledge is the largest reported cohort of patients with HR-MDS treated with HMAs in the United States. 16 Lenalidomide also is often attempted before specialty center referral, despite the limited efficacy of lenalidomide in the non-del5q setting and almost complete absence of activity in patients with HR-MDS.…”
Section: Introductionmentioning
confidence: 99%